2021
DOI: 10.1111/and.13983
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of administration and discontinuation of sildenafil and/or clomipramine on the hepatic, cardiac and testicular tissues of male rats

Abstract: In this study, we examined the adverse consequences of prolonged treatment with sildenafil and/or clomipramine (CLO) on the hepatic, cardiac and testicular tissues of rats. Additionally, we investigated the potential effects of treatment discontinuation. To this end, 60 adult male rats were randomly assigned into six groups and were orally treated with 4.5 mg sildenafil /kg BW (SLD) and 9 mg/ kg BW (SHD), 2.25 mg CLO/kg BW (CLO), 4.5 mg sildenafil/kg BW + 2.25 mg CLO/kg BW (SLD‐CLO) and 9 mg sildenafil/kg BW +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…In the present study, the histological examination of testicular sections from the non-diabetic group treated with high-dose sildenafil (13.5 mg) showed thickened tunica albuginea with mild sub-capsular edema, slightly distorted tubules with tunica propria, slightly diminished germinal lining and nearly complete spermatogenic layers in most of tubules, and normal interstitium with Leydig cells. These results were in agreement with Al-Fartosi 12 ; Alp et al 13 ; and El-Sheikh et al 14 who reported that most of tubules had normal architecture with some tubules had decreased germinal lining.…”
Section: Anatomy and Embryologysupporting
confidence: 91%
“…In the present study, the histological examination of testicular sections from the non-diabetic group treated with high-dose sildenafil (13.5 mg) showed thickened tunica albuginea with mild sub-capsular edema, slightly distorted tubules with tunica propria, slightly diminished germinal lining and nearly complete spermatogenic layers in most of tubules, and normal interstitium with Leydig cells. These results were in agreement with Al-Fartosi 12 ; Alp et al 13 ; and El-Sheikh et al 14 who reported that most of tubules had normal architecture with some tubules had decreased germinal lining.…”
Section: Anatomy and Embryologysupporting
confidence: 91%
“…Inflammation and oxidative stress are involved in the pathophysiology of nephrotoxicity and hepatotoxicity induced by many drugs ( Edrees et al, 2018 , El‐Sheikh et al, 2021a , El-Sheikh et al, 2021b ). Our results indicate that ASA treatment-induced inflammation and oxidant/antioxidant imbalance, which was manifested by a significant elevation of serum TNF-α (pro-inflammatory cytokine), MPO (A vital mechanistic link between inflammation and oxidation) ( Mostafa et al, 2018 ), MDA (lipid peroxidation biomarker) concentration as well as a significant reduction in GSH levels (non-enzymatic antioxidant), SOD and GPx activities (enzymatic antioxidant).…”
Section: Discussionmentioning
confidence: 99%
“…The rats were fasted overnight at the end of the study (10 days). They were weighed and sedated via intramuscular injection with a xylazine (5 mg/kg) and ketamine HCl (50 mg/kg) mixture ( El‐Sheikh et al, 2021a , El-Sheikh et al, 2021b ). A fine sterilized glass capillary tube was used to puncture the retroorbital venous plexus and collect blood samples.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies have shown the association between prolonged sildena l citrate utilization and the induction of oxidative stress, in ammatory responses, and structural changes within the testicular milieu. This long-term exposure has been linked to diminished sperm count and motility, elevated serum levels of testosterone (T), follicle-stimulating hormone (FSH), and luteinizing hormone (LH), as well as an escalated risk of penile brosis, culminating in irreversible damage to the corpus cavernosum tissue [25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%